Impact of COVID-19 pandemic on acute spine surgery referrals to UK tertiary spinal unit: any lessons to be learnt?. (4th March 2021) - Ahuja, Sashin; Shah, Pranav; Mohammed, Riaz
Abstract: Introduction: Evidence is emerging, suggesting a significant drop in hospital referrals and attendances for various medical conditions due to the COVID-19 pandemic. With the implementation of lockdown rules, road traffic and outdoor activities were expected to drop, thereby reducing the number of high-energy spinal injuries. Critical non-traumatic spinal conditions like spinal tumours, infections, or compressive pathologies, however, should continue to present as before. We assessed all acute spinal referrals to our tertiary spine unit comparing with the acute activity for a similar time frame in the previous year. The aim was to identify any variance in the acute spinal activity, explain reasons for the discrepancy and identify any learning points. Materials: All acute referrals to our tertiary spinal surgery unit made from 01 February 2020 to 30 April 2020 were evaluated. Similar data from the preceding year, i.e. 2019 was evaluated for comparison. Data were analysed for qualitative or quantitative changes in the referral pattern and their subsequent management outcomes. Results: Spinal referral numbers reduced by 46.05% during the time frame of February–April 2020 when compared to the same period in 2019 ( p  < 0.017). Similarly, numbers of high-energy traumatic presentations reduced by 72% ( p  < 0.002). Referrals for critical spinal conditions declined by two-thirds for spinal infections and more than a third for spinal tumours. Emergency surgical workload waned by 27%, especially more so during the six-week lockdown duration. Conclusion: Reduction in spinal activity, even for critical spinal conditions, during the pandemic is likely due to a combination of factors like patient behaviour, fear of contracting COVID-19 infection during hospital visit, self-isolation advice, availability of a senior decision maker on the frontlines, and changes in healthcare service provisions. The health crisis may provide an opportunity for optimisation of spinal healthcare services both at the referring hospital and at the tertiary centre.